2015
DOI: 10.1186/s13075-015-0721-3
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib (Tasigna™) in the treatment of early diffuse systemic sclerosis: an open-label, pilot clinical trial

Abstract: IntroductionTyrosine kinase inhibitors (TKI) are medications of interest in the treatment of Systemic Sclerosis (SSc) because of their ability to inhibit pathways involved in fibrosis. In this open-label pilot trial, our objectives were to assess the safety, efficacy, and molecular change associated with treatment of patients with diffuse cutaneous (dc)SSc with the TKI nilotinib (Tasigna™).MethodsTen adult patients with early dcSSc were treated with nilotinib. Primary endpoints were safety and change in modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 39 publications
1
64
0
Order By: Relevance
“…The weighted proportion of QTc prolongation of any grade with nilotinib was 2.7% with QTc of >500 ms, seen in 0.3% of cases. Caution and periodic ECG monitoring are advised when using nilotinib 71, 73, 74, 76, 77, 79, 80. QTc prolongation was common (37%) in patients with hepatic impairment treated with bosutinib,10 but this was not seen in other smaller studies 11, 12.…”
Section: Resultsmentioning
confidence: 98%
“…The weighted proportion of QTc prolongation of any grade with nilotinib was 2.7% with QTc of >500 ms, seen in 0.3% of cases. Caution and periodic ECG monitoring are advised when using nilotinib 71, 73, 74, 76, 77, 79, 80. QTc prolongation was common (37%) in patients with hepatic impairment treated with bosutinib,10 but this was not seen in other smaller studies 11, 12.…”
Section: Resultsmentioning
confidence: 98%
“…We identified 4 clinical microarray gene expression datasets from the NCBI's Gene Expression Omnibus (GEO) database comprising 282 samples obtained from skin ( Figure 1 and Supplemental Table 1; supplemental material available online with this article; doi:10.1172/jci.insight.89073DS1) (7,(10)(11)(12), which were derived from healthy control subjects, patients with diffuse cutaneous SSc or limited cutaneous SSc, and with various disease duration. Two of these datasets profiled longitudinally collected samples from study participants during treatment with rituximab (10) and nilotinib (7). Furthermore, we generated whole-genome transcriptional profiles for 3 additional cohorts, referred to as the Northwestern cohort, the UCSF2 cohort, and the Stanford cohort.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence supports the use of skin, lung, and peripheral blood transcriptomes as SSc biomarkers to quantify interpatient heterogeneity, to identify dysregulated molecular pathways underlying disease, and to identify appropriate patients for specific SSc therapies (6)(7)(8)(9). These studies have identified remarkable homogeneity in skin biopsies obtained from the same patient such that transcriptomic profiles of clinically unaffected back and clinically affected forearm biopsies are nearly identical (10)(11)(12).…”
Section: Introductionmentioning
confidence: 94%
“…First, since SSc is a rare disease, clinical trials tend to have small sample sizes. Thus, few differentially expressed genes (DEGs) can be detected after multiple hypothesis testing correction (Chakravarty et al, 2015;Gordon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To gain mechanistic insight into the action of experimental therapies, clinical trials in SSc have collected genome-wide gene expression data from skin biopsies pre-and post-treatment (Chakravarty et al, 2015;Gordon et al, 2015;Rice et al, 2015a;Hinchcliff et al, 2013;Chung et al, 2009) (Martyanov et al Submitted). However, these studies in clinical trials face limitations.…”
Section: Introductionmentioning
confidence: 99%